p70S6K promotes IL-6-induced epithelial-mesenchymal transition and metastasis of head and neck squamous cell carcinoma - Wu, Dandan (Oncotarget, 2016)
Head and neck squamous cell carcinoma (HNSCC) is the fifth most common cancer worldwide and a common cause of cancer-related death, with a 5-year survival rate of less than 60%. IL-6 has been suggested to play an important role in cancer metastasis, but its mechanism in HNSCC has not been fully clarified. p70S6K has been reported to induce epithelial-mesenchymal transition (EMT) of ovarian cancer, but its role in HNSCC remains unknown. In this study, we found that p70S6K and IL-6 were upregulated in high-metastatic HNSCC cell lines that underwent EMT when compared to paired low-metastatic cell lines. Overexpression of p70S6K promoted EMT and migration of HNSCC cells, while downregulation of p70S6K attenuated IL-6-induced EMT and cell migration. Furthermore, IL-6-induced p70S6K activation was attenuated by inhibitors of the PI3K/Akt/mTOR, MAPK/ERK, and JAK/STAT3 signaling pathways, suggesting that it located downstream of these pathways. These findings suggest that p70S6K promotes IL-6-induced EMT and metastasis of HNSCC. Targeting p70S6K for HNSCC therapy may benefit patients through the inhibition of tumor growth, as well as metastasis.